Bacabot helps dyslexic children to read, count more easily - Borneo Post, (KK) (Borneo Post (KK), 2016)
SINTOK: A research team from Universiti Utara Malaysia (UUM) has successfully devised the Bacabot application to help and create an interest in children with dyslexia to learn more easily.